ANALISIS SIFAT MEKANIK MATERIAL KOMPOSIT DARI SERAT SABUT KELAPA - Jonathan . Oroh; Frans P Sappu; Romels Cresano Lumintang (Fakultas Teknik Jurusan Teknik Mesin Universitas Sam Ratulangi, 2012)
This research uses coco fiber having straight fiber orientation. Different volume fraction with alkali (NaOH) treatment for two hours and without treatment have applied in this work. This composite was manufactured by molding where Polyester BQTN 157 was used as matrix. Bending test was performed based on ASTM D 6110 standard. The aim of this research is to obtain the optimum bending strength of coco fiber composite for volume fraction of 0 % fiber and 100% resin, 10% fiber and 90% resin, 20% fiber and 80%resin, 30% fiber and 70% resin, 40% fiber and 60% resin, 50% fiber and 50% resin, 60% fiber and 40% resin, 70% fiber and 30% resin with alkali treatment for two hours and without treatment, and find the result of fracture at the specimens. Based on the test results, the mean bending modulus of elasticity for specimens without treatment is 619047.619 MPa. This value was obtained at volume fraction of 40% fiber and 60% resin. On the other hand, the mean bending modulus of elasticity for specimens with alkali treatment is 4893.410928 MPa. This value was obtained at volume fraction of 30% fiber and 70% resin. Finally, based on the observation, the type of fracture occurring on specimens is broken fiber.